-polynomial and deficient topological indices of identified graphs. Issue 1 (2nd January 2022) - Gaur, Ravi Ratn; Garg, Pravin
Abstract: To study the properties such as physical and chemical of compounds, the topological indices are introduced in chemical graph theory. These indices provide qualitative structure activity relationship (QSAR). Degree based topological indices are commonly used invariant in chemical graph theory. However, in this article, a new degree of vertices is introduced, called "deficiency degree". Further, we have computed five topological indices based on the deficiency degree like "deficient first Zagreb index, deficient generalized Randić index, deficient harmonic index, deficient inverse sum index, deficient augmented Zagreb index" for identified graphs using the M -polynomial of graph.